The image Illustrated the Confusion Matrix displays the quantities of true positives (TP), true negatives (TN), false positives (FP), and false negatives (FN) predicted by the pre-trained Naive Bayes model. - Sajid Ullah (8299908) (2025)
The rows denote the actual classes, whilst the columns signify the predicted classes. The diagonal elements represent the count of accurate predictions, and the off-diagonal elements denote misclassifications.